ER and doctors’ preparedness to manage status epilepticus: a multi-institutional survey from the Gaza Strip - Belal Aldabbour; Ayoub AbuNemer; Muhammed Ghazi Alfarra; Osama Aldabbour; Yousef Abu Zaydah; Haytham Abuzaid; Abd Al-Karim Sammour; Samah Elamassie; Ahmed Yassin (BMC Health Services Research, 2024)
Abstract Background Status epilepticus (SE) is a top neurological and medical emergency. Adequate staff knowledge and sufficient hospital resources are mandatory for timely management and better outcomes. This study aims to evaluate Palestinian ER doctors’ knowledge and beliefs towards SE and assess the state and availability of hospital resources needed to manage SE appropriately. Methods This cross-sectional study surveyed all ER doctors working in the six governmental hospitals in the Gaza Strip during June 2022. A questionnaire assessed the knowledge and beliefs toward SE and the practice of SE knowledge acquisition. Simultaneous field surveys determined the availability of essential medications and resources at each hospital and doctors’ actual awareness about the status of these resources. Linear regression determined predictors of higher knowledge scores. Results 137 doctors participated (response rate 81%). Most were males, had graduated within six years of data collection, and 45.3% worked at Shifa Medical Complex. 63.5% of participants recognized the correct operational definition of status epilepticus. 85.4 and 83.9% recognized that it might cause permanent brain damage or death, respectively. Only 10.9% recognized the average mortality rate of a single convulsive SE episode. 44.5% believed that awaiting spontaneous SE resolution is a valid approach to management. Significant defects were noted in the awareness of subclinical SE, including its recognition and prevalence in ciritcally ill patients. Having a higher qualification and graduating from local medical schools predicted higher scores. In field surveys, EEG was unavailable at all hospitals, while CT scans and a neurologist physician were unavailable at two hospitals. IV phenytoin was the only second-line treatment available at all hospitals. IV valproate and levetiracetam were universally unavailable. Conclusions The survey revealed significant defects in Palestinian ER doctors’ knowledge and beliefs towards SE. Several hospitals also demonstrated a critical lack of resources to manage this condition appropriately. This should be addressed by the local health authorities to avoid potentially preventable SE-related mortality and morbidity.